Social arenas in the open habitat: the social role of waterholes for saiga antelope - Giljov, Andrey; Karenina, Karina (THERYA, 2024)
In wild animals, specific locations may function as ‘social arenas’ playing a significant role in various aspects of intraspecific interactions. The emergence of such social arenas is assumed to be particularly important under conditions of low visibility and density of individuals typical for forest dwelling species. In the forest, open areas with a high probability of meeting conspecifics such as waterholes and mineral licks can favor socialization. The paucity of studies on the open-habitat species limits our understanding of whether forest habitat is an essential condition for the emergence of social arenas. Here we address this issue by investigating whether resource hotspots function as social arenas in a species adapted to open habitat. The social behaviour in groups of saiga antelopes (Saiga tatarica tatarica) was recorded at large permanent waterholes (serving also as mineral licks) and away from them in the steppe environment. The frequency and variety of social interactions between the group mates were compared with a special effort made to minimize the potential impact of other factors besides the location. Also the focal individuals, interacting or not interacting with conspecifics at the waterholes, were traced continuously to explore the duration of their visit at the waterhole area. Finally, we recorded the number of individuals in the groups entering and leaving the waterhole. Active social interactions between group members occurred more often and were more varied near the waterholes as compared to the areas away from them. The participation in social interactions influenced the duration of individual waterhole visits. Males that interacted with others shortly after arrival stayed significantly longer compared to those who did not. Females whose calves engaged in social interactions with age-mates spent more time at the waterholes than females whose calves did not. The comparison of mean group sizes showed that saigas left waterhole areas in larger groups than they entered them. Our findings, together with previous studies, suggest that resource hotspots can function as social arenas in mammals regardless of the habitat type (open or closed). The emergence of specific locations having particular social significance may be especially important for highly dispersed species with large home ranges. The results of the study emphasize the significance of large permanent waterholes and mineral licks used by many individuals year after year for the social behaviour of saiga antelopes.